Revisiting the Nexus between Economic Policy Uncertainty, Financial Development, and FDI Inflows in Pakistan during Covid-19: Does Clean Energy Matter? - Serfraz, Ayesha; Qamruzzaman, Md.; Karim, Salma (International Journal of Energy Economics and Policy, 2023)
The significance of FDI for economic progress has been well established, especially for developing nations; conversely, the critical role of macro determinants has also been explained in attracting FDI. the motivation of the study is to assess the impact of economic policy uncertainty, financial development and clean energy on FDI in Pakistan economy. the study employed several econometric tools in assessing and documenting the elasticities of EPU, FD and CE in the process of amplifying the inflows of FDI in Pakistan. According to the study findings, it is apparent that financial development and clean energy positively affect FDI, while the effects of EPU are established as adversely connected to FDI. Study findings suggest, in Pakistan, for attracting and targeting the continual inflows of FDI, it is imperative to offer economic sustainability and efficient financial intermediation.